PENGARUH PROFITABILITAS, LIKUIDITAS DAN KEBIJAKAN DIVIDEN TERHADAP KUALITAS LABA (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019) - Teguh Erawati; Sintiya Arum Sari (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2021)
The purpose of this research to determine the effect of profitability, liquidity, and dividend policy on earnings quality. Population of this research is all of listed manufacturing firms in Bursa Efek Indonesia (BEI) in 2017-2019. The research sample consisted of 26 companies after the selection through purposive sampling method. his research data uses secondary research data in the form of financial reports which are downloaded from www.idx.co.id. The research data were analyzed using multiple linear analysis. The result show that profitability has a negative effect on earnings quality, dividend policy has a positive effect on earnings quality, while liquidity has no effect on earnings quality.